2015
DOI: 10.1016/j.neuroscience.2015.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of docosahexaenoic acid-containing phosphatidylcholine levels in the anterior horn of an ALS mouse model

Abstract: In this study, we analyzed the spatiotemporal alterations of phospholipid composition in the spinal cord of an amyotrophic lateral sclerosis (ALS) mouse model (G93A-mutated human superoxide dismutase 1 transgenic mice [SOD1(G93A) mice]) using imaging mass spectrometry (IMS), a powerful method to visualize spatial distributions of various types of molecules in situ. Using this technique, we deciphered the phospholipid distribution in the pre-symptomatic stage, early stage after disease onset, and terminal stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…We have compared metabolites altered in this in vitro ALS model to those found in the ALS mouse model (Patin et al, ) and in ALS patients (Blasco et al, ; Wuolikainen et al, ) (Table 4). We observed that in ALS‐associated condition, astrocytes displayed a low level of glycerophosphocholine as found in SOD1 G93A transgenic mice and additionally showed a decreased level of docosahexaenoic acid (DHA) as previously reported in SOD1 G93A mice (Arima et al, ). Phospholipids are used to synthesize sphingomyelins and are involved in the production of membranes (Moore et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…We have compared metabolites altered in this in vitro ALS model to those found in the ALS mouse model (Patin et al, ) and in ALS patients (Blasco et al, ; Wuolikainen et al, ) (Table 4). We observed that in ALS‐associated condition, astrocytes displayed a low level of glycerophosphocholine as found in SOD1 G93A transgenic mice and additionally showed a decreased level of docosahexaenoic acid (DHA) as previously reported in SOD1 G93A mice (Arima et al, ). Phospholipids are used to synthesize sphingomyelins and are involved in the production of membranes (Moore et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, we found a variety of glycerophospholipids decreased in this condition. Such a decrease was already shown in a SOD1-mouse model of ALS and could be related to the neuronal loss observed in these animals [36]. One possible hypothesis is that TDP-43 alters the composition of the cellular membrane and renders it more permeable (following the membrane hypothesis of aging [37]).…”
Section: Alteration Of Cell Metabolome Induced By Tdp-43 Overexpressionmentioning
confidence: 71%
“…The identification of the fatty acid chain 22:6 in the discriminant PCs of this model may correspond to the docosahexaenoic acid (DHA) involved in the maintenance of neuronal membranes, signal transduction, neuronal differentiation, neurogenesis, protection against synaptic loss, or spinal cord injury 21 . Whereas some authors have reported an association between the loss of motor neurons in the spinal cord in ALS model mice and the reduction in PC (diacyl-16:0/22:6) 22 , others have highlighted the significant increase of DHA in the frontal cortex of ALS patients 23 .…”
Section: Discussionmentioning
confidence: 99%